Cortisol Regulates Acid Secretion of H+-ATPase-rich Ionocytes in Zebrafish (Danio rerio) Embryos - Lin, Chia-Hao; Shih, Tin-Han; Liu, Sian-Tai; Hsu, Hao-Hsuan; Hwang, Pung-Pung (Frontiers in Physiology, 2015)
Systemic acid-base regulation is vital for physiological processes in vertebrates. Freshwater (FW) fish live in an inconstant environment, and thus frequently face ambient acid stress. FW fish have to efficiently modulate their acid secretion processes for body fluid acid-base homeostasis during ambient acid challenge; hormonal control plays an important role in such physiological regulation. The hormone cortisol was previously proposed to be associated with acid base regulation in FW fish; however, the underlying mechanism has not been fully described. In the present study, mRNA expression of acid-secreting related transporters and cyp11b (encoding an enzyme involved in cortisol synthesis) in zebrafish embryos was stimulated by treatment with acidic FW (AFW, pH 4.0) for 3 d. Exogenous cortisol treatment (20 mg/L, 3 d) resulted in upregulated expression of transporters related to acidsecretionand increased acid secretion function at the organism level in zebrafish embryos. Moreover, cortisol treatment also significantly increased the acid secretion capacity of H+-ATPase-rich cells (HRCs) at the cellular level. In loss-of-function experiments, microinjection of glucocorticoid receptor (GR) morpholino (MO) suppressed the expression of acid-secreting related transporters, and decreased acid secretion function at both the organism and cellular levels; on the other hand, mineralocorticoid receptor (MR) MO did not induce any effects. Such evidence supports the hypothesized role of cortisol in fish acid-base regulation, and provides new insights into the roles of cortisol; cortisol-GR signaling stimulates zebrafish acid secretion function through transcriptional/translational regulation of the transporters and upregulation of acid secretion capacity in each acid-secreting ionocyte.